Comparative analysis of ultrasound guided central venous catheterization compared to blind cateterisation. - Sazdov D; Jovanovski -Srceva M; Nikolova Todorova Z (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/ Sciendo, 2017)
introduction: Central venous catheterization is performed by the landmark method and ultrasound guided meth- od. The purpose of the study was to compare the success, average number of attempts, average time to return of blood, and complication rate between the two methods. Material and Methods: This was a prospective study done in the Intensive Care Unit of the Acibadem Sistina Clinical Hospital, in Skopje. There were 400 patients in need of central venous catheter and they were prospectively randomized in two groups. The patients randomized in the examined-ultrasound group underwent real-time ultrasound-guided catheterization and the patients randomized in the control-landmark group were catheterized using the landmark method. Internal Jugular, Subclavian and Femoral vein were catheterized in both groups. The Overall success, success on the first attempt, time to the return of blood, number of attempts and complications at the moment of catheterization such as arterial puncture, pneumothorax and hematoma formation were the main outcome measures. results: The catheterization using the landmark method was successful in 90.5% of patients, 60.5% of which during the first attempt. The cannulation using real-time ultrasound guidance was success- ful in 98% of patients with a first pass success of 77%. The complication rate with the landmark method was 14.5% versus 4% with real-time ultrasound guidance p<0.05(p=0.0008). conclusion: Real-time ultrasound guidance improves success, decreases number of attempts, decreases average time to the return of blood and reduces mechanical complications rate
Keywords: Landmark; ultrasound; central venous catheterisation